2010
DOI: 10.5539/ijms.v2n1p36
|View full text |Cite
|
Sign up to set email alerts
|

Third Screen Communication and the Adoption of Mobile Marketing: A Malaysia Perspective

Abstract: This study integrates innovation characteristics of the Innovation-Diffusion Theory (IDT), perceived risk, trustworthiness, and permissibility constructs to investigate what determines user intention to adopt mobile marketing. The proposed model in this study was empirically tested using data collected from a survey of mobile users. The structural equation modelling (SEM) technique was used to evaluate the causal model. The research findings suggested that relative advantage of mobile marketing is the stronges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 26 publications
0
30
0
2
Order By: Relevance
“…This attribute is often seen extending a direct significant negative influence on the users' adoption intentions and use decisions, some example studies of which are a service innovation-adoption study by Frambach, Barkema, Nooteboom, and Wedel (1998), a study on structural equation modelling by Brumec (2006), an automatic cash payment systems adoption study by Yang, Lai, and Tsai (2006), and a mobile-marketing adoption study by Tanakinjal, Deans, and Gray (2010). The level of ease or complexity involved in operating the IRCTC ticketing application on mobile is bound to be perceived differently by different users.…”
Section: Complexitymentioning
confidence: 98%
“…This attribute is often seen extending a direct significant negative influence on the users' adoption intentions and use decisions, some example studies of which are a service innovation-adoption study by Frambach, Barkema, Nooteboom, and Wedel (1998), a study on structural equation modelling by Brumec (2006), an automatic cash payment systems adoption study by Yang, Lai, and Tsai (2006), and a mobile-marketing adoption study by Tanakinjal, Deans, and Gray (2010). The level of ease or complexity involved in operating the IRCTC ticketing application on mobile is bound to be perceived differently by different users.…”
Section: Complexitymentioning
confidence: 98%
“…Electronic Commerce Research and Applications (2) Benamati et al, 2010;Faqih, 2012;Han and Han, 2009;Han and Jin, 2009;Hongxia et al, 2011;Hu et al, 2009;Hu et al, 2012;Jiang, 2009;Jou et al, 2011;Lee, 2009;Lorenzo-Romero et al, 2011;Liu and Forsythe, 2011;Luo et al 2010;San Martin Gutiérrez et al, 2010;Sawng et al, 2011;Shen and Chiou, 2010;Taylor and Strutton, 2010;Ting Pan and Cao, 2011;Tsai and Yeh, 2010;Udo et al, 2010 sequences of using the system (Lee 2009;Tanakinjal et al 2010). For instance, people may feel a certain level of risk when purchasing a product through a new technology (i.e.…”
Section: Behavioural Controlmentioning
confidence: 99%
“…Based upon past empirical studies (Lee 2009;Tanakinjal et al 2010;Gupta and Xu 2010), perceived risk is reported to be an impending factor for consumers to engage online shopping and it negatively influences the behavioural intention to use online channel for purchases. Hence, this variable is strictly connected to the perceived security.…”
Section: Consumer's Personal Traitsmentioning
confidence: 99%
“…Therefore complexity is assumed to be negatively associated to use intentions. A mobile marketing adoption study shows that complexity has a direct influence on user's adoption intentions (Tanakinjal, 2010). Studies on online portal use (Shih, 2008) and automatic cash payment system (Yang et al, 2006) found, complexity had a significant negative impact on use intention.…”
Section: Complexitymentioning
confidence: 99%